STRATEGIC BUSINESS SYNERGY IN HEALTH SERVICES: ANALYSIS OF THE DEVELOPMENT OF GF RANCABOLANG (GF RCB) PHARMACY AND DOCTOR CLINIC - Fajar Maully Pratama; Yenny Maya Dora (ZILLZELL MEDIA PRIMA, 2026)
This business plan aims to analyze the financial feasibility and development prospects of the GF Rancabolang Pharmacy and Medical Clinic (GF RCB) as an integrated health service (one-stop service) that combines medical practice and medicine provision. This plan was developed based on the increasing community need for accessible, fast, and high-quality health services. The analysis was conducted using a quantitative approach through investment feasibility indicators, namely Payback Period, Net Present Value (NPV), Return on Investment (ROI), and Profitability Index (PI). The results of the calculations show that the initial investment of IDR 540,000,000 is feasible. The Payback Period was achieved in 1.26 years (±15 months), indicating a quick return on investment. The NPV value of IDR 526,859,000 shows that the project generates positive economic benefits, while the ROI of 79% and PI of 1.98 prove that this venture provides a high level of profit. The 2025–2029 financial projections show an increase in revenue from IDR 2.2billion to IDR 3.22 billion, as well as an increase in net profit after tax from IDR 429 million to IDR 761 million. Thus, the development of the GF Rancabolang Pharmacy and Clinics declared feasible, profitable, and has long-term growth prospects.